Place after prison: neighborhood attachment and attainment during reentry - Simes, Jessica T. (Journal of urban affairs, 2018)
Over 600,000 people leave prison and become residents of neighborhoods across the United States annually. Using a longitudinal survey of people returning to Greater Boston, this study examines disparities in neighborhood attainment after prison. Accounting for levels of pre-prison neighborhood disadvantage, Black and Hispanic respondents moved into significantly more disadvantaged areas than whites. Forty percent of respondents initially moved to only one of two Boston community areas. Housing is an important neighborhood sorting mechanism: living in concentrated disadvantage was more likely for those residing in household arrangements with family or friends, or in emergency or transitional housing. Significantly, neighborhood residence was not attained by all: a quarter of respondents left prison and entered formal institutional settings or lived in extreme social marginality throughout Boston. Housing insecurity, re-incarceration, and profound racial disparities in neighborhood context explain the ecological structure of social inequality in urban neighborhoods in an era of mass incarceration.Accepted manuscrip